POLITIK PORK BARREL: BANTUAN SOSIAL (BANSOS) JOKOWI MENJELANG PEMILIHAN PRESIDEN 2024 - Muhammad Ishak Syahadat; Iriyani Astuti Arief; La Ode Efrianto (Halu Oleo University, 2024)
This study explores the phenomenon of pork barrel politics in the context of social assistance (bansos) distribution ahead of Indonesia's 2024 Presidential and Vice-Presidential Election. The primary focus is on how President Joko Widodo leveraged social assistance as a political tool to boost the electability of his endorsed candidates, Prabowo Subianto and Gibran Rakabuming Raka. Using a distributive politics framework and pork barrel theory, this research analyzes the patterns of social assistance distribution in regions with high voter registration, such as Central Java, East Java, and West Java. The findings indicate a discriminatory strategy in the allocation of social assistance to support specific candidates, achieved through the strategic deployment of government funds. This study contributes to the understanding of distributive politics practices in the context of Indonesian electoral politics, with implications for transparency and accountability in the management of public budgets.